Numerical and experimental investigation on the mechanism of synchronous trailing cold air heat sink in eliminating the deformation during laser welding SUS301L thin sheet. (September 2022) - Liu, Zuguo; Jin, Xiangzhong; Zhang, Junyi; Hao, Zhongjia; Li, Junhao; Chen, Huiyang
Highlights: Welding distortion prediction and mitigation of SUS301 stainless steel sheet with thermo-elastic-plastic FE analysis is demonstrated. 2A hybrid welding method combining laser welding and Vortex tube compressed air refrigeration (VTCAR) heat sink techniques was further investigated. Tendon force was introduced to evaluate welding induced buckling deformation and stress under different heat sink processes. A finite element model was established to analyze heat sink assisted laser welding SUS301 stainless steel with thickness of 0.6 mm. The stress and deformation mechanisms are numerically analyzed based on the inherent strain theory. Abstract: In order to control and eliminate the welding induced welding deformation of thin stainless steel a laser welding method assisted by a new type of synchronous trailing cold air heat sink is first proposed in this paper. This kind of heat sink is obtained by using vortex tube compressed air refrigeration (VTCAR), which is safe, of low cost and easy to be implemented compared with other commonly used heat sinks such as argon-water mixture, liquid nitrogen, etc. Then, a thermo-elastic-plastic multi physical field coupling numerical model of laser welding with a cold air heat sink located at the rear of laser beam is established, and the effects of the places where the VTCAR heat sink is exerted and heat sink parameters including the heat sink strength and the distance between the heat sink and the laser beam on the welding induced welding deformation are numerically studied. Such two cases as the heat sink is located on the top and bottom surface of the sample respectively are considered. The simulation results show that the cold source exerted on the top surface has the more significant effect than that on the bottom surface under the same heat sink parameters, and the position of heat sink, exactly speaking, the distance between the cold source and the laser beam, has a decisive effect on reducing welding induced buckling. The smaller the distance, the smaller the welding induced buckling. At the heat sink strength of 200 ml and the distance of 5 mm, the equivalent residual stress decreases by 8.09%, and the maximum welding induced deformation decreases by 31.62%. Thirdly, experiments of laser welding with a synchronous trailing VTCAR heat sink are carried out onSUS301L thin sheet. It can be seen that the specimen appears a saddle shape after welding. The coordinate values of the points on the outer plane of the post weld specimen are measured by three coordinates measuring machine, from which the actual welding deformation can be obtained. Both the specimen shape and the measured welding deformation value are in good agreement with the simulation results based on the large deformation theory, which verifies the correctness and the accuracy of the above simulation model. Finally, the mechanism of the synchronous trailing VTCAR heat sink in eliminating the deformation is discussed by inherent strain theory. In the cooling stage during laser welding, the heat sink not only reduces the temperature field of the base metal near the weld, but also makes the typical comet characteristics at the tail of the weld pool disappear and become a flat temperature profile, which effectively reduces the temperature gradient in the weld area and weakens the longitudinal tensile plastic strain of the weld specimens, and eventually reduces Tendon force and the welding inherent strain. There is a high consistency between Tendon force and the welding deformation, so Tendon force can be taken as the basis for evaluating the welding induced welding deformation.